Hydrophobic modification of nanoscale zero-valent iron with excellent stability and floatability for efficient removal of floating oil on water. (June 2018) - Peng, Ziling; Xiong, Chunmei; Wang, Wei; Tan, Fatang; Wang, Xinyun; Qiao, Xueliang; Wong, Po Keung
Abstract: Usually, nanoscale zero-valent iron (NZVI) cannot float on water because of high density and hydrophilic surface. Herein, alkyltrimethoxysilanes with different carbon chain lengths (C1, C8 and C16) were used as "water-repellent legs" to graft onto NZVI, enduing NZVI with hydrophobic and floatable characteristics like a water strider. The hydrophobic performance of as-modified NZVI materials was found to be better when NZVI was modified by alkyltrimethoxysilane with longer carbon chain, and a large contact angle of 151.2°(>150°) was obtained in C16-NZVI, indicating the superhydrophobic characteristic of C16-NZVI. The oil-absorption experiments showed that the absorption capacity of C16-NZVI for lubricating oil reached 9.73 g/g within 30 s. After seven consecutive runs, the oil-absorption capacity of C16-NZVI still maintained at 9.26 g/g, indicating high reusability of C16-NZVI. Also, C16-NZVI exhibited excellent stability in NaCl solution without being oxidized for 32 d. Significantly, C16-NZVI possessed admirable chemical stability with high hydrophobic property in acid and alkaline solutions (pH 3–12). Considering the advantages of easy preparation, high stability and reusability, excellent oil-absorption capacity as well as magnetic recovery property, C16-NZVI is expected to have remarkable potential in the treatment of floating oil on water/seawater. Graphical abstract: Image 1 Highlights: Floatable NZVI was obtained by modifying of alkyltrimethoxysilane. The contact angle of hexadecyltrimethoxysilane-modified NZVI(C16-NZVI) was 151.2°. The absorption capacity of C16-NZVI for lubricating oil reached 9.73 g/g. C16-NZVI possessed good stability and reusability in 3.5% NaCl solution. C16-NZVI had excellent magnetic property to facilitate separation and recovery.